Disaster Tips for People with Disabilities - Carolyn S. Wilken (EDIS)
Natural disasters such as tornadoes, floods, and hurricanes create special challenges for people with disabilities, their caregivers, and their families. People with disabilities need to have the same basic disaster supply kit as everyone else. Basic supply lists are available from a number of sources, but the list available at the American Red Cross web site serves as the model (http://www.redcross.org/disaster/safety/fds-all.pdf). People with disabilities may have special needs that go beyond the basic supplies list. The tips in this document were recommended by the U.S. Departments of Homeland Security and the Federal Emergency Management Agency for people with disabilities. This document is FCS9215, one of a series of the Family Youth and Community Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: August 2005.